Intentional mentoring: maximizing the impact of underrepresented future scientists in the 21st century. Issue 6 (20th July 2021) - Shuler, Haysetta; Cazares, Victor; Marshall, Andrea; Garza-Lopez, Edgar; Hultman, Rainbo; Francis, Tam'ra-Kay; Rolle, Tiffany; Byndloss, Mariana X; Starbird, Chrystal A; Hicsasmaz, Innes; AshShareef, Salma; Neikirk, Kit; et al.
ABSTRACT: Mentoring is a developmental experience intended to increase the willingness to learn and establish credibility while building positive relationships through networking. In this commentary, we focus on intentional mentoring for underrepresented mentees, including individuals that belong to minority racial, ethnic and gender identity groups in Science, Technology, Engineering, Mathematics and Medicine (STEMM) fields. Intentional mentoring is the superpower action necessary for developing harmony and comprehending the purpose and value of the mentor/mentee relationship. Regardless of a mentor's career stage, we believe the strategies discussed may be used to create a supportive and constructive mentorship environment; thereby improving the retention rates of underrepresented mentees within the scientific community. Abstract : This article discusses how to be an intentional mentor in the 21st Century.